2013
DOI: 10.1371/journal.pone.0059069
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Structure and Molecular Dynamics Simulations of Endoglucanase 3 from Trichoderma harzianum: Structural Organization and Substrate Recognition by Endoglucanases That Lack Cellulose Binding Module

Abstract: Plant biomass holds a promise for the production of second-generation ethanol via enzymatic hydrolysis, but its utilization as a biofuel resource is currently limited to a large extent by the cost and low efficiency of the cellulolytic enzymes. Considerable efforts have been dedicated to elucidate the mechanisms of the enzymatic process. It is well known that most cellulases possess a catalytic core domain and a carbohydrate binding module (CBM), without which the enzymatic activity can be drastically reduced.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 56 publications
2
20
0
2
Order By: Relevance
“…For example, loop 3 of some Aspergillus endoglucanases that contain [T/S]TTQA are much longer, while those from Trichoderma, Penicillium, Thielavia, and Fusarium contain [F/M/V/S]N instead. It has been reported that Asn152 of loop 3 of ThEG3 from T. harzianum forms a hydrogen bond with substrate (25). These findings suggest that loop 3 may have varied roles in catalysis.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…For example, loop 3 of some Aspergillus endoglucanases that contain [T/S]TTQA are much longer, while those from Trichoderma, Penicillium, Thielavia, and Fusarium contain [F/M/V/S]N instead. It has been reported that Asn152 of loop 3 of ThEG3 from T. harzianum forms a hydrogen bond with substrate (25). These findings suggest that loop 3 may have varied roles in catalysis.…”
Section: Discussionmentioning
confidence: 90%
“…The docking grid size was set to 66 Å by 66 Å by 66 Å, which was placed in an appropriate cavity in the catalytic pocket. The docked complexes were analyzed to select the most reliable binding conformation, as performed in previous studies (4,25). Molecular dynamics (MD) simulations were carried out using the Amber ff99SB force field at a temperature of 338 K (328 K for complexes EG and the EGΔSTTQA mutant with ligands) for 32 ns.…”
Section: Strainsmentioning
confidence: 99%
“…A cleft structure of the hydrophobic residues (yellow) of carbohydrate-binding module family 4. Reproduced with permission from (Prates et al 2013).…”
Section: Fundamentals Of Cellulose Binding Domainsmentioning
confidence: 99%
“…There have been many crystallization and structure analysis studies both for endoglucanases [7][8][9][10][11] and cellobiohydrolases [12][13][14][15][16][17] purified by several sources. These studies mainly focus on the structure of the catalytic core domain.…”
Section: Introductionmentioning
confidence: 99%